2019
DOI: 10.1051/ctv/20193401048
|View full text |Cite
|
Sign up to set email alerts
|

Application of soy protein isolate in the fining of red wine

Abstract: Soy protein isolate was evaluated as a potential fining agent as an alternative to the predominant protein commercial fining agents (ovalbumin, porcine gelatin, and pea protein isolate). Two red wines (cv. ‘Merlot’ and cv. ‘Lambrusco Maestri’) were finned, bottled, and analyzed for phenolic content, color, turbidity, and sensory profile. Independent of the protein used, fining promoted a reduction in a majority of the phenolic compound, a slight (but significant) reduction of chromatic properties, and a decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…However with the discovery of the transmissible nature of Bovine Spongiform Encephalopathy (BSE) and due to the concerns about the potential risk of allergies and food intolerance from products of animal origin, the search for a new protein source was initiated (Marchal et al, 2002;Maury et al, 2003;Jiménez-Martínez et al, 2017). On recent works, it is observed that vegetable proteins are as effective as proteins of animal origin in the fining of red wines (Ben Aziz et al, 2017;Granato et al, 2018;Ficagna et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However with the discovery of the transmissible nature of Bovine Spongiform Encephalopathy (BSE) and due to the concerns about the potential risk of allergies and food intolerance from products of animal origin, the search for a new protein source was initiated (Marchal et al, 2002;Maury et al, 2003;Jiménez-Martínez et al, 2017). On recent works, it is observed that vegetable proteins are as effective as proteins of animal origin in the fining of red wines (Ben Aziz et al, 2017;Granato et al, 2018;Ficagna et al, 2019).…”
Section: Introductionmentioning
confidence: 99%